Maternal Predator Odor Exposure in Mice Programs Adult Offspring Social Behavior and Increases Stress-Induced Behaviors in Semi-Naturalistic and Commonly-Used Laboratory Tasks - St-Cyr, Sophie; Abuaish, Sameera; Spinieli, Richard L.; McGowan, Patrick O. (Frontiers in Behavioral Neuroscience, 2018)
Maternal stress has a profound impact on the long-term behavioral phenotype of offspring, including behavioral responses to stressful and social situations. In this study, we examined the effects of maternal exposure to predator odor, an ethologically relevant psychogenic stressor, on stress-induced behaviors in both semi-naturalistic and laboratory-based situations. Adult C57BL/6 mice offspring of dams exposed to predator odor during the last half of pregnancy showed increased anti-predatory behavior, more cautious foraging behavior and, in the elevated plus maze, avoidance of elevated open areas and elevated open areas following restraint stress challenge. These offspring also exhibited alterations in social behavior including reduced free interaction and increased initial investigation despite normal social recognition. These changes in behavior were associated with increased transcript abundance of corticotropin-releasing factor, mineralocorticoid receptor and oxytocin in the periventricular nucleus of the hypothalamus. Taken together, the findings are consistent with a long-term increase in ethologically-relevant behavioral and neural responses to stress in male and female offspring as a function of maternal predator odor exposure.